2017
DOI: 10.1002/ijc.31207
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer‐associated mitochondrial DNA haplogroup promotes neoplastic growth via ROS‐mediated AKT activation

Abstract: In the last decade, mitochondrial DNA (mtDNA) haplogroups have been associated with the occurrence of breast cancer. However, the underlying mechanism is not known. Combining a case-control study with a large cohort of women from Southern China with breast cancer and functional analyses with trans-mitochondrial technology, we demonstrate that the D5 haplogroup is associated with an increased risk of breast cancer [odds ratio (OR) = 2.789; 95% confidence interval (CI) [1.318, 5.901]; p = 0.007]. Furthermore, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…We found a higher frequency of the D haplogroup (12%) than in previously published works about the Mexican-Mestizo population (6.2%) (50,51). The D haplogroup has been associated with predisposition to breast cancer in the Chinese population and experimental data revealed that the D5 branch haplogroup promotes tumorigenesis through AKT activation, mediated by a high concentration of reactive oxygen species (ROS) (52,53). However, we need to include more patients and to perform a case-control analysis to determine whether the haplogroup D has clinical significance in Mexican women with breast cancer.…”
Section: Native American Haplogroups In Mexican Women With Breast Tumorsmentioning
confidence: 49%
“…We found a higher frequency of the D haplogroup (12%) than in previously published works about the Mexican-Mestizo population (6.2%) (50,51). The D haplogroup has been associated with predisposition to breast cancer in the Chinese population and experimental data revealed that the D5 branch haplogroup promotes tumorigenesis through AKT activation, mediated by a high concentration of reactive oxygen species (ROS) (52,53). However, we need to include more patients and to perform a case-control analysis to determine whether the haplogroup D has clinical significance in Mexican women with breast cancer.…”
Section: Native American Haplogroups In Mexican Women With Breast Tumorsmentioning
confidence: 49%
“…Recently, PI3K/Akt has been associated with osteosarcoma progression and resistance to chemotherapeutic drugs. [39][40][41][42] BzATP increased Akt activity, but P2X7 receptor inhibition significantly reduced Akt phosphorylation in HOS/MNNG cells. Treatment with a PI3K inhibitor, LY294002, resulted in significantly reduced cell proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 90%
“…The PI3K/Akt signaling cascade plays a critical role in tumor cell growth and bioenergetics, regulating aerobic glycolysis, cell cycle progression and autophagy. Recently, PI3K/Akt has been associated with osteosarcoma progression and resistance to chemotherapeutic drugs . BzATP increased Akt activity, but P2X7 receptor inhibition significantly reduced Akt phosphorylation in HOS/MNNG cells.…”
Section: Discussionmentioning
confidence: 98%
“…Germline and somatic mutations in mtDNA have been studied in breast cancer in various populations across the world (26,29,30,47). Certain studies have suggested a positive correlation between specific D-loop mutations and haplogroups (48)(49)(50), and the risk of breast cancer. Therefore, mtDNA may serve as a potential biomarker for the early diagnosis of breast cancer, and its relevance may be dependent on ethnicity (21,51).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations Patients Controls 1 73G, 150T, 195C, 240G, 263G, 315.1C, 16129A, 16266T, 16311C, 16318G, 16320T, 0 2 16362C, 16519C 2 73G, 195A, 263G, 315.1C, 489C, 523d, 524d, 16223T, 16519C 1 2 the Sri Lankan population, where a majority belonged to the M haplogroup followed by the N haplogroup and its derivatives (28). Other studies have reported an association between haplogroups and breast cancer, such as haplogroup D5 and M in the Chinese population (49,59,60) and haplogroup N in the Indian population (57,61). Whilst the Sinhalese population was not associated with a macro-haplogroup, the haplogroup M65a@16311 was observed in a number of patients and the haplogroup M30 was observed in a number of controls.…”
Section: Haplotypementioning
confidence: 98%